Resin composition, resin sheet, laminate, and circuit board material
A resin composition with 20% thermoplastic resin and specific additives achieves low dielectric properties and strong adhesion to conductors, addressing the limitations of conventional resins in high-frequency applications.
Patent Information
- Application Number
- JP2023116169
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
Smart Images

Figure 2025012954000001 
Figure 2025012954000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a resin sheet, a laminate, and a circuit board material. [Background technology]
[0002] In recent years, as electrical and electronic devices have become more powerful and functional, communication frequencies have become higher in order to improve communication speeds and the amount of information transmitted. When a digital signal is transmitted through a circuit board, a portion of the transmitted digital signal is converted into heat within the circuit board, resulting in transmission loss. Since the amount of transmission loss is expressed as the product of the dielectric constant and the dielectric loss tangent, a material with a low dielectric constant and dielectric loss tangent, i.e., a component with low dielectric properties, is required to achieve low-loss communication. Since transmission signals in the high-frequency range in particular are more easily converted into heat, materials with even lower dielectric properties are in demand. Furthermore, in the case of high-frequency circuit boards, like conventional ones, components are mounted and connections to other circuit boards are made through processes such as solder reflow and hot bar soldering, so the circuit board materials are also required to have heat resistance.
[0003] Known examples of materials having low dielectric properties include polyphenylene ether resin compositions containing an epoxy compound and a cyanate compound (see, for example, Patent Document 1), thermosetting resins such as maleimide resins (see, for example, Patent Document 2), and thermoplastic resins such as cyclic olefin resin compositions (see, for example, Patent Document 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-059363 A [Patent Document 2] JP 2012-255059 A [Patent Document 3] International Publication No. 2006 / 095511 Summary of the Invention [Problem to be solved by the invention]
[0005] However, conventional thermosetting resins tend to have higher dielectric constants and dielectric loss tangents than thermoplastic resins, and it has been necessary to add large amounts of inorganic particles or the like to achieve low dielectric properties. On the other hand, conventional thermoplastic resins have low dielectric properties but often lack good heat resistance. Furthermore, when the above-mentioned materials are used as circuit board materials, they are laminated with a conductor such as copper foil, and therefore are required to have an adhesive strength that does not cause peeling or deformation from the conductor.
[0006] Therefore, an object of the present invention is to provide a resin composition, a resin sheet, a laminate and a circuit board material which have low dielectric properties and excellent adhesion to conductors. [Means for solving the problem]
[0007] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that a resin composition comprising at least one thermoplastic resin (A) selected from the group consisting of a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, and an ethylene-based polymer, a radically polymerizable compound (B), an epoxy compound (C), and a curing agent (D), wherein the content of the thermoplastic resin (A) is 20 mass% or more relative to the total mass of the resin composition, and the sum of the contents of the epoxy compound (C) and the curing agent (D) is more than 0 mass% and less than 4 mass% relative to the total mass of the resin composition, can achieve both low dielectric properties and adhesion to an adherend, in particular a conductor.
[0008] The gist of the present invention is as follows. [1] A resin composition comprising at least one thermoplastic resin (A) selected from the group consisting of a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, an ethylene-based polymer, and a cyclic polyolefin resin copolymer, a radically polymerizable compound (B), an epoxy compound (C), and a curing agent (D), wherein the content of the thermoplastic resin (A) is 20 mass% or more based on the total mass of the resin composition, and the sum of the contents of the epoxy compound (C) and the curing agent (D) is more than 0 mass% and less than 4 mass% based on the total mass of the resin composition. [2] The resin composition according to [1], comprising a styrene-based thermoplastic elastomer as the thermoplastic resin (A), wherein the styrene content of the styrene-based thermoplastic elastomer is 10% by mass or more and 70% by mass or less. [3] The resin composition according to [1] or [2], wherein the thermoplastic resin (A) has a mass average molecular weight (Mw) of 30,000 or more. [4] The resin composition according to any one of [1] to [3], wherein the content of the radical polymerizable compound (B) per 100 parts by mass of the thermoplastic resin (A) is 1 part by mass or more and 50 parts by mass or less. [5] The resin composition according to any one of [1] to [4], wherein the sum of the contents of the thermoplastic resin (A) and the radically polymerizable compound (B) is 30 mass% or more based on the total mass of the resin composition. [6] The resin composition according to any one of [1] to [5], wherein the epoxy compound (C) is a multifunctional epoxy compound having an epoxy equivalent of 1000 g / eq or less. [7] The resin composition according to any one of [1] to [6], wherein the curing agent (D) is an acid anhydride curing agent and / or an active ester curing agent. [8] The resin composition according to any one of [1] to [7], wherein a cured product obtained by heat pressing the resin composition at 200°C and 2 MPa for 30 minutes has a dielectric loss tangent of 0.003 or less at a frequency of 10 GHz. [9] A resin sheet comprising the resin composition according to any one of [1] to [8].
[10] A laminate comprising a release film on one or both surfaces of the resin sheet according to [9].
[11] A circuit board material comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to [8] and a conductor laminated thereon. Effect of the Invention
[0009] According to the present invention, it is possible to obtain a resin composition, a resin sheet, a laminate, and a circuit board material which have low dielectric properties and excellent adhesion to a conductor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An example of an embodiment of the present invention will be described in detail below, however, the present invention is not limited to the embodiment described below. In the present invention, the term "film" conceptually includes a sheet, a film, and a tape. Furthermore, when the term "panel" is used, such as an image display panel or a protective panel, it encompasses a plate, a sheet, and a film.
[0011] In the present invention, when it is described as "x to y" (x and y are any numbers), unless otherwise specified, it includes the meaning of "greater than x and less than y", as well as "preferably greater than x" or "preferably smaller than y". In addition, when it is stated that the amount is "x or more" (where x is any number), it also means that the amount is "preferably greater than x" unless otherwise specified, and when it is stated that the amount is "y or less" (where y is any number), it also means that the amount is "preferably smaller than y" unless otherwise specified. Furthermore, "x and / or y (x and y are optional configurations)" means at least one of x and y, and means the following three cases: x only, y only, and x and y. In addition, in the present invention, "(meth)acrylic" refers to a comprehensive definition of acrylic and methacrylic, "(meth)acrylate" refers to a comprehensive definition of acrylate and methacrylate, and "(meth)acryloyl" refers to a comprehensive definition of acryloyl and methacryloyl.
[0012] <Resin composition> A resin composition according to one embodiment of the present invention (hereinafter also referred to as "the resin composition") contains at least one thermoplastic resin (A) selected from the group consisting of a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, an ethylene-based polymer, and a cyclic polyolefin resin copolymer, a radically polymerizable compound (B), an epoxy compound (C), and a curing agent (D). Each component of the resin composition will now be described.
[0013] 1. Thermoplastic resin (A) The thermoplastic resin (A) of the present resin composition is at least one selected from the group consisting of styrene-based thermoplastic elastomers, olefin-based thermoplastic elastomers, ethylene-based polymers, and cyclic polyolefin resin copolymers.
[0014] Examples of the styrene-based thermoplastic elastomer include styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), and hydrogenated versions of these, such as styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene-propylene-styrene block copolymer (SEPS), and styrene-isobutylene-styrene block copolymer (SIBS).
[0015] The olefin-based thermoplastic elastomer contains a polyolefin (excluding cyclic polyolefins, which will be described later) as a hard segment, and a rubber component as a soft segment. The olefin-based thermoplastic elastomer may be a mixture (polymer blend) of a polyolefin and a rubber component, a crosslinked product obtained by crosslinking a polyolefin with a rubber component, or a polymer obtained by polymerizing a polyolefin with a rubber component. The polyolefin includes polypropylene, polyethylene, and the like. Examples of the rubber component include diene rubbers such as isoprene rubber, butadiene rubber, butyl rubber, propylene-butadiene rubber, acrylonitrile-butadiene rubber, and acrylonitrile-isoprene rubber; ethylene-propylene non-conjugated diene rubber; and ethylene-butadiene copolymer rubber.
[0016] The ethylene polymer includes a homopolymer of ethylene and a copolymer of ethylene and another monomer. The copolymer of ethylene and another monomer preferably contains ethylene as a main component. Here, "containing ethylene as a main component" means that the copolymer contains 50 mol % or more, preferably 60 mol % or more, of ethylene structural units. The other monomer to be copolymerized with ethylene is not particularly limited as long as it is a monomer copolymerizable with ethylene. Preferred examples of the ethylene polymer include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), polyethylene obtained by polymerization using a metallocene catalyst, etc. Among these, it is particularly preferable to use linear low-density polyethylene (LLDPE) because of its high flexibility.
[0017] The cyclic polyolefin resin copolymer is a copolymer having an alicyclic structure, specifically, a copolymer having an alicyclic structure in the side chain of polyolefin.Preferable examples of the alicyclic structure include cycloalkane, bicycloalkane, polycyclic compound, etc. Among these, cycloalkane is preferred, and cyclohexane is more preferred. The alicyclic structure is more preferably an alicyclic structure generated by hydrogenation of an aromatic ring contained in a hydrogenated aromatic vinyl polymer block unit described below.
[0018] The cyclic polyolefin resin copolymer preferably has a crystal melting peak temperature of less than 100°C. The crystalline melting peak temperature of the cyclic polyolefin resin copolymer is preferably 50° C. or higher, more preferably 60° C. or higher, and even more preferably 65° C. or higher. The crystalline melting peak temperature of the cyclic polyolefin resin copolymer is preferably 90° C. or lower, and more preferably 85° C. or lower. The crystalline melting peak temperature in the present invention is the temperature at which a crystalline melting peak is detected in differential scanning calorimetry (DSC) measured at a heating rate of 10° C. / min. The cyclic polyolefin resin copolymer used in the present resin composition may have a crystalline melting peak at less than 100° C., and may have a crystalline melting peak at two points, for example, less than 100° C. and 100° C. or higher.
[0019] Examples of known cyclic polyolefins include hydrogenated ring-opening polymers having repeating units derived from monocyclic norbornene monomers or polycyclic norbornene monomers (e.g., International Publication Nos. WO 2012 / 046443 and WO 2012 / 033076). These cyclic polyolefins have an alicyclic structure in the polymer main chain, and either do not have a crystalline melting peak temperature below 100° C. or are amorphous. On the other hand, the cyclic polyolefin resin copolymer of the present resin composition has an alicyclic structure in the polyolefin side chain, and therefore has a crystal melting peak temperature below 100°C.
[0020] The melt flow rate (MFR) of the cyclic polyolefin resin copolymer is not particularly limited, but is usually 0.1 g / 10 min or more, and from the viewpoint of molding method and appearance of molded body, it is preferably 0.5 g / 10 min or more. The melt flow rate (MFR) is usually 200 g / 10 min or less, and from the viewpoint of material strength, it is preferably 100 g / 10 min or less, more preferably 90.0 g / 10 min or less. By setting the MFR within the above range, compatibility with the thermoplastic resin described later is improved. The MFR is determined in accordance with ISO R1133, by measuring at a temperature of 230°C and a load of 2.16 kg.
[0021] <Cyclic polyolefin (a)> As the cyclic polyolefin resin copolymer used in the present resin composition, from the viewpoint of low dielectric properties, a cyclic polyolefin containing at least one type of hydrogenated aromatic vinyl polymer block unit and at least one type of hydrogenated conjugated diene polymer block unit (hereinafter also referred to as "cyclic polyolefin (a)"), or a modified product of the cyclic polyolefin (a) with at least one of an unsaturated carboxylic acid and an anhydride thereof is preferred.
[0022] For purposes of this invention, "block" refers to a polymeric segment of a copolymer that exhibits microphase separation from structurally or compositionally distinct polymeric segments of the copolymer. Microphase separation occurs due to the immiscibility of the polymeric segments in the block copolymer. Microphase separation and block copolymers are extensively discussed in "Block Copolymers - Designer Soft Materials" in the February 1999 issue of PHYSICS TODAY, pp. 32-38.
[0023] Examples of the cyclic polyolefin (a) include a diblock copolymer consisting of a hydrogenated aromatic vinyl polymer block unit (hereinafter also referred to as "block A") and a hydrogenated conjugated diene polymer block unit (hereinafter also referred to as "block B"), a triblock copolymer containing two or more of at least one of block A and block B, a tetrablock copolymer, and a pentablock copolymer. The cyclic polyolefin (a) preferably contains at least two blocks A, and suitable examples thereof include an ABA type, an ABAB type, and an ABABA type.
[0024] In addition, the cyclic polyolefin (a) preferably contains a segment made of an aromatic vinyl polymer at each end. For this reason, the hydrogenated block copolymer of the present resin composition preferably has at least two hydrogenated aromatic vinyl polymer block units (blocks A) and at least one hydrogenated conjugated diene polymer block unit (block B) between the two hydrogenated aromatic vinyl polymer block units (blocks A). From these viewpoints, the cyclic polyolefin (a) is more preferably an ABA type or an ABABA type.
[0025] The content of the hydrogenated aromatic vinyl polymer block unit (block A) in the cyclic polyolefin (a) is preferably 30 to 99 mol %, more preferably 40 to 90 mol %, still more preferably 50 mol % or more, and even more preferably 60 mol % or more. If the ratio of the hydrogenated aromatic vinyl polymer block unit (block A) is equal to or higher than the lower limit, the rigidity is not decreased and the heat resistance and the linear thermal expansion coefficient are also good. On the other hand, if the ratio is equal to or lower than the upper limit, the flexibility is good.
[0026] The content of the hydrogenated conjugated diene polymer block unit (block B) in the cyclic polyolefin (a) is preferably 1 to 70 mol %, more preferably 10 to 60 mol %, still more preferably 50 mol % or less, and even more preferably 40 mol % or less. When the ratio of the hydrogenated conjugated diene polymer block unit (block B) is equal to or higher than the lower limit, the flexibility is good. On the other hand, when the ratio is equal to or lower than the upper limit, the rigidity is not decreased and the heat resistance and the linear thermal expansion coefficient are also good.
[0027] The hydrogenated aromatic vinyl polymer block unit and the hydrogenated conjugated diene polymer block unit constituting the cyclic polyolefin (a) can be obtained by hydrogenating a polymer block composed of an aromatic vinyl monomer and a conjugated diene monomer such as 1,3-butadiene, which will be described in detail later. Also, the cyclic polyolefin (a) is preferably a block copolymer having no functional groups. The term "no functional groups" means that the block copolymer has no functional groups, i.e., no groups containing atoms other than carbon and hydrogen atoms.
[0028] The monomers for forming the aromatic vinyl polymer block unit and the conjugated diene polymer block unit before hydrogenation will be described below.
[0029] (Aromatic vinyl monomer) The aromatic vinyl monomer serving as a raw material for the aromatic vinyl polymer block unit before hydrogenation is a monomer represented by the following general formula (1).
[0030] [ka]
[0031] In the above general formula (1), R is hydrogen or an alkyl group, and Ar is a phenyl group, a halophenyl group, an alkylphenyl group, an alkylhalophenyl group, a naphthyl group, a pyridinyl group, or an anthracenyl group.
[0032] When R is an alkyl group, the carbon number is preferably 1 to 6, and the alkyl group may be mono- or polysubstituted with functional groups such as a halo group, a nitro group, an amino group, a hydroxyl group, a cyano group, a carbonyl group, and a carboxyl group. Moreover, the above Ar is preferably a phenyl group or an alkylphenyl group, and more preferably a phenyl group.
[0033] Examples of aromatic vinyl monomers include styrene, α-methylstyrene, vinyltoluene (including all isomers, with p-vinyltoluene being particularly preferred), ethylstyrene, propylstyrene, butylstyrene, vinylbiphenyl, vinylnaphthalene, vinylanthracene (including all isomers), and mixtures thereof. Among these, styrene is preferred.
[0034] (Conjugated Diene Monomer) The conjugated diene monomer serving as the raw material of the conjugated diene polymer block unit before hydrogenation is not particularly limited as long as it is a monomer having two conjugated double bonds. Conjugated diene monomers include, for example, 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2-methyl-1,3-pentadiene and similar compounds, and mixtures thereof. Of these, 1,3-butadiene is preferred.
[0035] When 1,3-butadiene is used as the conjugated diene monomer, its polymer, polybutadiene, contains 1,4-bond units ([-CH2-CH=CH-CH2-]) and 1,2-bond units ([-CH2-CH(CH=CH2)-]), and the former gives a structure similar to the repeating unit of polyethylene (ethylene structure) upon hydrogenation, and the latter gives a structure similar to the repeating unit when 1-butene is polymerized (1-butene structure). Therefore, the hydrogenated conjugated diene polymer block in the present resin composition preferably contains at least one of an ethylene structure and a 1-butene structure. Furthermore, when isoprene is used as the conjugated diene monomer, its polymer, polyisoprene, contains 1,4-bond units ([-CH2-C(CH3)=CH-CH2-]), 3,4-bond units ([-CH2-CH(C(CH3)=CH2)-]), and 1,2-bond units ([-CH2-C(CH3)(CH=CH2)-]), and contains at least one of the three types of repeating units obtained by hydrogenation.
[0036] (Block structure) The cyclic polyolefin (a) is preferably produced by hydrogenation of a multiblock copolymer such as a triblock copolymer, a tetrablock copolymer, or a pentablock copolymer, such as SBS, SBSB, SBSBS, SBSBSB, SIS, SISIS, and SISBS (where S is polystyrene, B is polybutadiene, and I is polyisoprene). The block may be a linear block or may be branched. When branched, the polymerization chain may be bonded at any position along the backbone of the copolymer. In addition to a linear block, the block may be a tapered block or a star block.
[0037] The block copolymer constituting the cyclic polyolefin (a) before hydrogenation may contain one or more additional block units other than the aromatic vinyl polymer block unit and the conjugated diene polymer block unit. For example, in the case of a triblock copolymer, these additional block units may be bonded to any position of the triblock polymer backbone.
[0038] A preferred example of the hydrogenated aromatic vinyl polymer block unit is hydrogenated polystyrene, and a preferred example of the hydrogenated conjugated diene polymer block unit is hydrogenated polybutadiene or hydrogenated polyisoprene, with hydrogenated polybutadiene being more preferred. A preferred embodiment of the cyclic polyolefin (a) is a hydrogenated triblock or pentablock copolymer of styrene and butadiene, with a hydrogenated triblock copolymer being more preferred.
[0039] (Hydrogenation level) The cyclic polyolefin (a) is a polyolefin in which the aromatic rings derived from styrene and the like are hydrogenated in addition to the double bonds derived from conjugated dienes such as butadiene, and is substantially completely hydrogenated. Specifically, it refers to a polyolefin that has achieved the following hydrogenation levels: The hydrogenation level of the hydrogenated aromatic vinyl polymer block unit is preferably 90% or more, more preferably 95% or more, further preferably 98% or more, and particularly preferably 99.5% or more. The hydrogenation level of the hydrogenated conjugated diene polymer block unit is preferably 95% or more, more preferably 99% or more, and even more preferably 99.5% or more. Such a high level of hydrogenation reduces dielectric loss and also provides good stiffness and heat resistance. The hydrogenation level of the hydrogenated aromatic vinyl polymer block unit refers to the proportion of the aromatic vinyl polymer block unit saturated by hydrogenation, and the hydrogenation level of the hydrogenated conjugated diene polymer block unit refers to the proportion of the conjugated diene polymer block unit saturated by hydrogenation. The hydrogenation level of each block unit is determined using proton NMR.
[0040] The cyclic polyolefin (a) may be used alone or in combination of two or more kinds. As the cyclic polyolefin (a) in the present resin composition, commercially available products can be used, specifically, TEFABLOC (registered trademark) manufactured by Mitsubishi Chemical Corporation can be mentioned.
[0041] Among the above thermoplastic resins (A), from the viewpoints of low dielectric properties and ease of processing, styrene-based thermoplastic elastomers are preferred, and styrene-ethylene-butadiene-styrene block copolymers (SEBS) are more preferred. In addition, among the thermoplastic resins (A) exemplified above, when a combination in which the thermoplastic resin (A) itself is difficult to react with the radical polymerizable compound (B) is selected, the thermoplastic resin (A) and the radical polymerizable compound (B) form an interpenetrating polymer network structure (hereinafter also referred to as a "semi-IPN structure"), which is considered to improve low dielectric properties and heat resistance. The semi-IPN structure is a structure in which the molecular chains of the thermoplastic resin (A) and the radical polymerizable compound (B) are partially and physically entangled with each other, rather than the thermoplastic resin (A) and the radical polymerizable compound (B) forming a chemical bond. By forming this semi-IPN structure, the crosslink density is increased in a pseudo manner compared to the thermoplastic resin (A) alone, while maintaining the low dielectric properties of the thermoplastic resin (A). Therefore, it is considered that the elastic modulus is improved and the heat resistance is improved. From this viewpoint, among the above-mentioned thermoplastic resins (A), styrene-based thermoplastic elastomers are preferred, styrene-isobutylene-styrene block copolymers (SIBS) or styrene-ethylene-butadiene-styrene block copolymers (SEBS) are more preferred, and styrene-ethylene-butadiene-styrene block copolymers (SEBS) are even more preferred.
[0042] When a styrene-based thermoplastic elastomer is used as the thermoplastic resin (A), the styrene content in the styrene-based thermoplastic elastomer is preferably 10% by mass or more, more preferably 15% by mass or more. The upper limit of the styrene content is preferably 70% by mass or less, more preferably 65% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, and particularly preferably 40% by mass or less. When the styrene content is within the above range, the thermoplastic resin (A) has a low dielectric tangent and an appropriate elastic modulus, so that low dielectric properties and heat resistance can be achieved at the same time, and handling properties are also good.
[0043] From the viewpoint of improving heat resistance and dimensional stability while maintaining low dielectric properties, it is preferable that the thermoplastic resin (A) contains at least one selected from the group consisting of a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, and an ethylene-based polymer (hereinafter also referred to as (A1)), and a cyclic polyolefin resin copolymer (hereinafter also referred to as (A2)). The reason why the heat resistance of the cured product of the above resin composition is good is not clear, but it is thought that when a resin composition containing at least one thermoplastic resin (A1) selected from the group consisting of a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, and an ethylene-based polymer as the thermoplastic resin (A), and a cyclic polyolefin resin copolymer (A2), is cured, the crosslink density is artificially increased by the radical polymerizable compound (B) entangled with the (A1) and the cyclic polyolefin resin copolymer (A2), thereby improving the elastic modulus. In addition, the reason why the dimensional stability of the cured product of the resin composition is improved is unclear, but the more alicyclic structures contained in the cured product, the lower the linear thermal expansion coefficient and the more the dimensional stability tends to be improved. Therefore, it is considered that the inclusion of the cyclic polyolefin resin copolymer (A2) as the thermoplastic resin (A) relatively increases the alicyclic structure compared to the case of using the thermoplastic resin (A1) alone. Among the above (A1), from the viewpoints of low dielectric properties and processability, styrene-based thermoplastic elastomers are preferred, and styrene-ethylene-butadiene-styrene block copolymers (SEBS) are more preferred.
[0044] The mass average molecular weight (Mw) of the thermoplastic resin (A) is preferably 30,000 or more, more preferably 40,000 or more, and even more preferably 50,000 or more from the viewpoint of preventing tackiness in the resulting resin sheet, while being preferably 300,000 or less, more preferably 250,000 or less, and even more preferably 200,000 or less from the viewpoint of handling during film formation. In the present invention, the weight average molecular weight (Mw) is a value calculated as polystyrene equivalent and measured by gel permeation chromatography.
[0045] The thermoplastic resin (A) may be modified by a known method. Examples of the modified product include a reaction product of the above-mentioned thermoplastic resin (A) with at least one of an unsaturated carboxylic acid and an acid anhydride. By modifying the thermoplastic resin (A), the polarity of the polymer increases, and this is expected to improve adhesion to conductors such as copper foil.
[0046] Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, α-ethylacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, methyltetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, and nadic acids. Of these, acrylic acid, maleic acid, and nadic acid are preferred. Examples of the acid anhydride include the anhydrides of the above unsaturated carboxylic acids as well as maleic anhydride, citraconic anhydride, and nadic anhydrides, with maleic anhydride and nadic anhydride being preferred. Examples of nadic acids include endo-cis-bicyclo[2.2.1]hept-2,3-dicarboxylic acid (nadic acid) and methyl-endo-cis-bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic acid (methylnadic acid). These may be used alone or in combination of two or more.
[0047] The content of the thermoplastic resin (A) in the resin composition is 20% by mass or more based on the total mass of the resin composition. By having the content of the thermoplastic resin (A) of 20% by mass or more, it is possible to obtain a cured product that has excellent low dielectric properties, is highly flexible, and is excellent in handleability. From this viewpoint, the content is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more. The upper limit of the content is not particularly limited, but from the viewpoint of enhancing adhesiveness, it is preferably 99% by mass or less, more preferably 97% by mass or less, even more preferably 95% by mass or less, even more preferably 90% by mass or less, even more preferably 80% by mass or less, particularly preferably 75% by mass or less, and most preferably 70% by mass or less. In this specification, the total mass of the resin composition means the sum of the components constituting the resin composition excluding the solvent (F) described below.
[0048] When the thermoplastic resin (A) contains the thermoplastic resin (A1) and the cyclic polyolefin resin copolymer (A2), the mass ratio of the thermoplastic resin (A1) to the cyclic polyolefin resin copolymer (A2) is preferably (A2) / (A1)=10 / 90 to 90 / 10, more preferably 15 / 85 to 80 / 20, and even more preferably 20 / 80 to 70 / 30. When the mass ratio is within the above range, the sheet cured product has a good balance of moldability, dielectric properties, etc.
[0049] The storage modulus of the thermoplastic resin (A) at 25°C is preferably 0.1 MPa or more, more preferably 1 MPa or more, even more preferably 5 MPa or more, and particularly preferably 10 MPa or more. The storage modulus is preferably 5000 MPa or less, more preferably 4000 MPa or less, more preferably 3000 MPa or less, even more preferably 2500 MPa or less, and among these, preferably 2000 MPa or less, more preferably 1000 MPa or less, even more preferably 500 MPa or less, even more preferably 300 MPa or less, even more preferably 100 MPa or less, and even more preferably 50 MPa or less. By setting the storage modulus below the upper limit, the present resin composition has good flexibility when cured, whereas by setting the storage modulus to equal to or greater than the lower limit, the present resin composition has good heat resistance and handleability when cured.
[0050] The storage modulus can be determined by forming the thermoplastic resin (A) into a sheet having a thickness of 300 μm to prepare a test piece, and measuring the dynamic viscoelasticity with a viscoelasticity spectrometer.
[0051] The density of the thermoplastic resin (A) is 0.98 g / cm 3 Less than 0.95 g / cm is preferred. 3 Less than 0.91 g / cm is more preferable. 3 On the other hand, the lower limit of the density is not particularly limited, but is preferably 0.80 g / cm3 or less. 3 The above is preferred. When the density is equal to or less than the above value, the present resin composition has good flexibility when cured.
[0052] The density can be measured in accordance with ASTM D792 by forming the thermoplastic resin (A) into a sheet having a thickness of 300 μm into a test piece.
[0053] The dielectric loss tangent of the thermoplastic resin (A) is preferably less than 0.005 at 10 GHz, more preferably less than 0.003, even more preferably less than 0.002, and particularly preferably less than 0.001. On the other hand, the lower limit is not particularly limited as long as it is 0 or more. The smaller the dielectric tangent, the smaller the dielectric loss, and therefore when the resin composition is used as a circuit board material, the transmission efficiency and speed of electric signals can be increased.
[0054] The dielectric loss tangent can be determined by forming the thermoplastic resin (A) into a sheet having a thickness of 300 μm to prepare a test piece, and measuring the test piece at a temperature of 23° C. and a frequency of 10 GHz in accordance with JIS C2565:1992.
[0055] 2. Radical polymerizable compound (B) The radically polymerizable compound (B) in the present resin composition is a compound having two or more carbon-carbon double bonds in the molecule, and these can be used alone or in combination of two or more kinds. The mass average molecular weight (Mw) of the radical polymerizable compound (B) is preferably 100 or more, and more preferably 120 or more. The mass average molecular weight (Mw) is preferably 4,000 or less, more preferably 3,000 or less, even more preferably 2,000 or less, even more preferably 1,000 or less, still more preferably 800 or less, and particularly preferably 600 or less. When the mass average molecular weight (Mw) of the radical polymerizable compound (B) is within the above range, foaming due to decomposition of the radical polymerizable compound (B) during curing is suppressed, and the molecular chains of the hydrocarbon-based polymer compound (A), the radical polymerizable compound (B), and the epoxy compound (C) are easily entangled with each other, making it easier to increase the crosslinking density in a pseudo manner, and therefore the heat resistance and dimensional stability of the obtained sheet cured product are improved. In addition, when the crosslinking agent is not partially crosslinked or polymerized, the "mass average molecular weight (Mw) of the radically polymerizable compound (B)" means the molecular weight of the compound used as the radically polymerizable compound (B).
[0056] Examples of the functional group having a carbon-carbon double bond include a vinyl group, an acryloyl group, and a methacryloyl group. Among these, a vinyl group is preferred from the viewpoints of improving compatibility with the thermoplastic resin (A) and reducing the dielectric tangent of the obtained sheet cured product.
[0057] Examples of the bifunctional radically polymerizable compound (B) include bifunctional aromatic vinyl compounds such as divinylbenzene, divinylnaphthalene, and divinylbiphenyl; ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, and the like. difunctional aliphatic (meth)acrylate compounds such as 2-methyl-1,3-propanediol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, glycerin di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, and ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate;Cyclohexanedimethanol di(meth)acrylate, ethoxylated cyclohexanedimethanol di(meth)acrylate, propoxylated cyclohexanedimethanol di(meth)acrylate, ethoxylated propoxylated cyclohexanedimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethoxylated tricyclodecane dimethanol di(meth)acrylate, propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated propoxylated tricyclodecane dimethanol di(meth)acrylate Bifunctional alicyclic (meth)acrylate compounds such as chlodecane dimethanol di(meth)acrylate, ethoxylated hydrogenated bisphenol A di(meth)acrylate, propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated hydrogenated bisphenol F di(meth)acrylate, propoxylated hydrogenated bisphenol F di(meth)acrylate, and ethoxylated propoxylated hydrogenated bisphenol F di(meth)acrylate; ethylenedioxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated bisphenol AF di(meth)acrylate, propoxylated bisphenol AF di(meth)acrylate, ethoxylated propoxylated bis Examples of the difunctional aromatic (meth)acrylate compounds include phenol AF di(meth)acrylate, ethoxylated fluorene type di(meth)acrylate, propoxylated fluorene type di(meth)acrylate, and ethoxylated propoxylated fluorene type di(meth)acrylate; and difunctional heterocyclic (meth)acrylate compounds include ethoxylated isocyanuric acid di(meth)acrylate, propoxylated isocyanuric acid di(meth)acrylate, and ethoxylated propoxylated isocyanuric acid di(meth)acrylate.
[0058] Examples of the trifunctional or higher radical polymerizable compound (B) include triallyl cyanurate and triallyl isocyanurate compounds such as triallyl cyanurate and triallyl isocyanurate; trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, and ethoxylated propoxylated pentaerythritol tri(meth)acrylate. polyfunctional aliphatic (meth)acrylate compounds such as pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetraacrylate, and dipentaerythritol hexa(meth)acrylate; and polyfunctional heterocyclic (meth)acrylate compounds such as ethoxylated isocyanuric acid tri(meth)acrylate, propoxylated isocyanuric acid tri(meth)acrylate, and ethoxylated propoxylated isocyanuric acid tri(meth)acrylate.
[0059] Among the above, from the viewpoint of compatibility with the thermoplastic resin (A), bifunctional aromatic vinyl compounds and trialkenyl isocyanurate compounds are preferred, and from the viewpoint of low dielectric properties, divinylbenzene or trialkenyl isocyanurate compounds are more preferred.
[0060] The radical polymerizable compound (B) preferably has no polar functional group or has a small number of polar functional groups in the molecule. When the radical polymerizable compound (B) has a cyclic structure, it is preferable that the substituent has no polar functional group or has a small number of polar functional groups. When the amount of polar functional groups is small, the compatibility with the thermoplastic resin (A) becomes good, and the dielectric loss tangent of the obtained sheet cured product also becomes low. The polar functional group means a functional group having a negative atom (e.g., nitrogen, oxygen, chlorine, fluorine, etc.) and having a net dipole. Examples of the functional group include an ester group, a carbonyl group, a carboxyl group, a hydroxyl group, an amide group, and an amino group. When the radical polymerizable compound (B) has an ester group, the polar functional group equivalent of the radical polymerizable compound (B) (molecular weight of the radical polymerizable compound (B) / molecular weight of the polar functional group (total amount when there are multiple polar functional groups)) is preferably 2 or more, more preferably 3 or more, even more preferably 4 or more, even more preferably 5 or more, and still more preferably 6 or more.
[0061] The content of the radically polymerizable compound (B) in the resin composition is preferably 1 part by mass or more and 50 parts by mass or less, more preferably 3 parts by mass or more and 30 parts by mass or less, even more preferably 5 parts by mass or more and 25 parts by mass or less, and even more preferably 10 parts by mass or more and 20 parts by mass or less, per 100 parts by mass of the thermoplastic resin (A). When the content of the radically polymerizable compound (B) is within the above range, compatibility with the thermoplastic resin (A) is good and it becomes easier to increase the crosslinking density in a pseudo manner, so that the heat resistance of the obtained cured product is good.
[0062] The sum of the contents of the thermoplastic resin (A) and the radical polymerizable compound (B) is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more, based on the total mass of the resin composition. By setting the sum of the contents of the thermoplastic resin (A) and the radical polymerizable compound (B) within the above range, a cured product having excellent adhesiveness and low dielectric tangent can be obtained. The upper limit of the sum of the contents is not particularly limited, but from the viewpoint of improving adhesiveness, it is preferably 98% by mass or less, more preferably 97% by mass or less, and even more preferably 96% by mass or less.
[0063] 3. Epoxy compounds (C) The epoxy compound (C) in the resin composition is a compound having at least one epoxy group in one molecule. By including the epoxy compound (C), it is possible to obtain a resin composition having excellent adhesion to an adherend, particularly to a conductor such as copper. The epoxy compound (C) may be in a solid or liquid state, and one or more kinds may be used in combination.
[0064] Although thermoplastic resins such as styrene-based thermoplastic elastomers, olefin-based thermoplastic elastomers, and ethylene-based polymers are suitable as materials having low dielectric properties, when the above materials are used as circuit board materials, there is a problem that the adhesiveness is insufficient for laminating with a conductor such as copper foil. If an additive having a polar functional group is used to increase the adhesiveness, the compatibility with the thermoplastic resin is insufficient or the dielectric tangent of the resulting cured product becomes high, so that it has been desired to achieve both high adhesiveness and low dielectric properties at a higher level. Under these circumstances, the present inventors conducted extensive research and found that the use of a predetermined amount of an epoxy compound (C) and a curing agent (D) described below improves adhesion without impairing the low dielectric properties of the resin composition, thereby completing the present invention.
[0065] By using the epoxy compound (C), the glycidyl group of the epoxy compound (C) forms a chemical bond such as a covalent bond or a hydrogen bond with the interface of the adherend (e.g., metal foil, etc.), thereby improving the adhesion to the conductor. In addition, it has been found that by containing a predetermined amount of the epoxy compound (C) and the curing agent (D) described later, it is possible to allow a moderate amount of glycidyl groups to be present at the interface with the adherend while maintaining the flexibility of the cured product, and thus it is possible to more efficiently form chemical bonds and interactions with the adherend.
[0066] Examples of the epoxy compound (C) include monofunctional aliphatic epoxy compounds such as ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, 1,2-epoxytetradecane, and lauryl glycidyl ether; monofunctional fluorine-containing epoxy compounds such as 2-(trifluoromethyl)oxirane and 2,2,3,3,4,4,5,5,5-nonafluoropentyloxirane; bifunctional fluorine-containing epoxy compounds such as 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bis(oxirane); and monofunctional aromatic epoxy compounds such as o-phenylphenol glycidyl ether, phenyl glycidyl ether, 2-biphenylyl glycidyl ether, and 4-t-butylphenyl glycidyl ether.Aromatic epoxy compounds such as bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol C type epoxy compounds, bisphenol AF type epoxy compounds, naphthalene type epoxy compounds, biphenyl type epoxy compounds, resorcinol type epoxy compounds, phenol novolac type epoxy compounds, and cresol novolac type epoxy compounds, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, butanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, trimethylolpropane triglycidyl ether, Examples of the epoxy compounds include aliphatic epoxy compounds such as glycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitol polyglycidyl ether, cyclohexane diglycidyl ether, dicyclopentadiene diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, hydrogenated bisphenol F diglycidyl ether, hexahydrophthalic acid diglycidyl ester, vinyl(3,4-cyclohexene) dioxide, 2-(3,4-epoxycyclohexyl)-5,1-spiro-(3,4-epoxycyclohexyl)-m-dioxane, and epoxidized polybutadiene; and polyfunctional epoxy compounds such as heterocyclic epoxy compounds such as triglycidyl isocyanurate and hydantoin type epoxy compounds, halogenated epoxy compounds, glycidylamine type epoxy compounds, epoxy group-containing rubber compounds, epoxy group-containing polyurethane compounds, and epoxy group-containing acrylic compounds.
[0067] Among these, from the viewpoint of improving the adhesion to the adherend, polyfunctional epoxy compounds are preferred, and among these, epoxy compounds containing two or more epoxy groups in one molecule are more preferred. Moreover, from the viewpoint of compatibility with the present resin composition and maintaining appropriate flexibility, aliphatic epoxy compounds are preferred, and among these, alkylene glycol diglycidyl ethers are preferred from the viewpoint of excellent compatibility, and among these, hexanediol diglycidyl ether and tripropylene glycol diglycidyl ether are particularly preferred. Moreover, from the viewpoint of improving low dielectric properties, fluorine-containing epoxy resins are preferred, and among them, bisphenol AF type epoxy compounds are particularly preferred from the viewpoint of improving adhesion to insulating materials such as PTFE.
[0068] The epoxy equivalent of the epoxy compound (C) is preferably 1000 g / eq or less, more preferably 700 g / eq or less, and even more preferably 500 g / eq or less, from the viewpoint of compatibility with the thermoplastic resin (A) and the radically polymerizable compound (B). On the other hand, the lower limit is preferably 10 g / eq or more, more preferably 50 g / eq or more, from the viewpoint of increasing the crosslink density of the cured product and suppressing volatilization of the epoxy compound (C).
[0069] The content of the epoxy compound (C) is preferably 0.01 to 4 parts by mass, more preferably 0.03 to 3 parts by mass, further preferably 0.05 to 2 parts by mass, and particularly preferably 0.08 to 1 part by mass, relative to 100 parts by mass of the thermoplastic resin (A). When the content of the epoxy compound (C) is within the above range, the adhesiveness to the adherend tends to be improved while maintaining low dielectric properties.
[0070] 4. Hardener (D) The curing agent (D) refers to a substance that contributes to a crosslinking reaction and / or a chain extension reaction between epoxy groups of the epoxy compound (C). Examples of the curing agent (D) used in the present resin composition include phenol-based curing agents, acid anhydride-based curing agents, active ester-based curing agents, amide-based curing agents, cationic curing agents, etc. These may be used alone or in combination of two or more kinds.
[0071] Examples of the phenol-based curing agent include bisphenols such as bisphenol A, bisphenol F, bisphenol S, bisphenol B, bisphenol AD, bisphenol Z, and tetrabromobisphenol A, biphenols such as 4,4'-biphenol and 3,3',5,5'-tetramethyl-4,4'-biphenol, catechol, resorcin, hydroquinone, dihydroxynaphthalenes, and compounds in which the hydrogen atoms bonded to the aromatic rings of these compounds are substituted with non-interfering substituents such as halogen groups, alkyl groups, aryl groups, ether groups, ester groups, and organic substituents containing hetero elements such as sulfur, phosphorus, and silicon, as well as novolaks and resols which are polycondensates of the above-mentioned phenols, or monofunctional phenols such as phenol, cresol, and alkylphenols with aldehydes.
[0072] Examples of the acid anhydride curing agent include methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylhimic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylcyclohexene dicarboxylic anhydride, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol bistrimellitate, glycerol tristrimellitate, dodecenyl succinic anhydride, polyazelaic anhydride, and poly(ethyloctadecanedioic) anhydride.
[0073] The active ester curing agent is not particularly limited, but generally, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, polyarylates, and esters of heterocyclic hydroxy compounds, is preferred. The above-mentioned active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. From the viewpoint of improving heat resistance in particular, an active ester resin obtained from a carboxylic acid compound or its halide and a hydroxy compound is preferred, and an active ester resin obtained from a carboxylic acid compound or its halide and a phenol compound and / or a naphthol compound is more preferred.
[0074] Examples of the amide-based curing agent include dicyandiamide and its derivatives, polyamide resins, and the like.
[0075] The cationic polymerization curing agent generates cations by heat or active energy ray irradiation, and examples thereof include aromatic onium salts. - , BF4 - , AsF6 - , PF6 - , CF3SO3, B(C6F5)4 - and an aromatic cation component containing an atom such as iodine, sulfur, nitrogen, or phosphorus.
[0076] From the viewpoint of improving various properties such as heat resistance and adhesion, it is preferable that the curing agent (D) contains at least one type of curing agent selected from the group consisting of phenol-based curing agents, acid anhydride-based curing agents, and active ester-based curing agents. Among the above, acid anhydride-based curing agents and active ester-based curing agents are preferred from the viewpoints that no hydroxyl groups are generated in the reaction product with the epoxy compound (C) and the low dielectric properties of the cured product are easily maintained. In addition, when the resin composition contains the acid anhydride-based curing agent or the active ester-based curing agent, it is preferable to further contain a curing aid (F) described later together with the curing agent. By using the curing aid (F) in combination, the reaction of the epoxy compound (C) proceeds efficiently.
[0077] The sum of the contents of the epoxy compound (C) and the curing agent (D) is more than 0 mass% and less than 4 mass% with respect to the total mass of the resin composition. By having the sum of the contents of the epoxy compound (C) and the curing agent (D) in the above range, excellent adhesion can be obtained. From the above viewpoints, the sum of the contents of the epoxy compound (C) and the curing agent (D) is preferably more than 0 mass% and not more than 3.5 mass%, more preferably 0.2 to 3 mass%, and even more preferably 0.5 to 1 mass%, relative to the total mass of the resin composition.
[0078] The content of the curing agent (D) is preferably from 30 to 500 parts by mass, more preferably from 40 to 300 parts by mass, and further preferably from 50 to 200 parts by mass, relative to 100 parts by mass of the epoxy compound (C).
[0079] 5.Organic peroxide (E) The present resin composition may contain an organic peroxide (E) for the purpose of accelerating the curing reaction. Examples of the organic peroxide include those belonging to the group of hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxy esters, and ketone peroxides. Specific examples of the peroxides include hydroperoxides such as cumene hydroperoxide and tert-butyl hydroperoxide; dialkyl peroxides such as dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 2,5-bis(tert-butylperoxy)-2,5-dimethyl-3-hexyne; diacyl peroxides such as lauryl peroxide and benzoyl peroxide; peroxy esters such as tert-butyl peroxyacetate, tert-butyl peroxybenzoate and tert-butylperoxyisopropyl carbonate; and ketone peroxides such as cyclohexanone peroxide.
[0080] The content of the organic peroxide (E) in the present resin composition is preferably 0.01 parts by mass or more and 5 parts by mass or less, more preferably 0.05 parts by mass or more and 3 parts by mass or less, and even more preferably 0.1 parts by mass or more and 1 part by mass or less, per 100 parts by mass of the thermoplastic resin (A). When the content of the organic peroxide (E) is within the above range, the curing reaction can be promoted while the dielectric properties of the cured product can be maintained at a low level.
[0081] 6. Hardening agent (F) In addition to the above-mentioned components, the resin composition may further contain a curing aid (F) as an optional component. Examples of the curing assistant include organic phosphine curing assistants, phosphonium salt curing assistants, tetraphenyl boron salt curing assistants, metal curing assistants, imidazole curing assistants, amine curing assistants, organic acid dihydrazide curing assistants, boron halide amine complex curing assistants, etc. These curing assistants may be used alone or in any combination and ratio of two or more.
[0082] Organic phosphine curing assistants, phosphonium salt curing assistants, tetraphenylboron salt curing assistants Among the organic phosphine curing assistants, phosphonium salt curing assistants, and tetraphenylboron salt curing assistants, compounds that can be used as the curing assistant for the epoxy resin composition of the present invention include triphenylphosphine, diphenyl(p-tolyl)phosphine, tris(alkylphenyl)phosphine, tris(alkoxyphenyl)phosphine, tris(alkyl / alkoxyphenyl)phosphine, tris(dialkylphenyl)phosphine, tris(trialkylphenyl)phosphine, tris(tetraalkylphenyl)phosphine, tris(dialkoxyphenyl)phosphine, tris(trialkoxyphenyl)phosphine, tris(trialkylphenyl)phosphine, tris(trialk ... Examples of the organic phosphines include organic phosphines such as s(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, and alkyldiarylphosphine; complexes of these organic phosphines with organic borons; and compounds obtained by adding these organic phosphines to quinone compounds such as maleic anhydride, 1,4-benzoquinone, 2,5-toluquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, and phenyl-1,4-benzoquinone, and compounds such as diazophenylmethane.
[0083] The metal-based curing assistant is not particularly limited, and examples thereof include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, tin, etc. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate.
[0084] Examples of the organic metal salt include zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate. As the metal-based curing aid, from the viewpoints of curability and solvent solubility, cobalt(II) acetylacetonate, cobalt(III) acetylacetonate, zinc(II) acetylacetonate, zinc naphthenate, and iron(III) acetylacetonate are preferred, with cobalt(III) acetylacetonate and zinc naphthenate being particularly preferred.
[0085] Examples of the imidazole-based curing assistant include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[ Examples of imidazole compounds include 2'-methylimidazolyl-(1')-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5 hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins.
[0086] Examples of the amine-based curing aid include trialkylamines such as triethylamine and tributylamine; and amine compounds such as 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene (hereinafter abbreviated as DBU).
[0087] The content of the curing aid (F) in the present resin composition is, from the viewpoint of the progress of the curing reaction, preferably 0.01 mass % or more, more preferably 0.03 mass % or more, even more preferably 0.05 mass % or more, and is preferably 0.3 mass % or less, more preferably 0.2 mass % or less, even more preferably 0.1 mass % or less, relative to 100 parts by mass of the epoxy compound (C).
[0088] 7. Solvent (G) The present resin composition may contain a solvent (G) if necessary for viscosity adjustment or the like. The solvent (G) is not particularly limited as long as the components of the resin composition can be uniformly dissolved therein. Examples of the solvent (G) include toluene, cyclohexane, tetrahydrofuran, xylene, and methyl ethyl ketone. The above-mentioned solvents may be used alone or in any combination and ratio. The boiling point of the solvent (G) is preferably 200° C. or lower in order to reduce the amount of residual solvent.
[0089] From the viewpoint of film-forming properties, the content of the solvent (G) in the present resin composition is preferably from 100 to 500 parts by mass, more preferably from 200 to 400 parts by mass, per 100 parts by mass of the thermoplastic resin (A).
[0090] 8. Other Ingredients The resin composition may contain, as components other than those described above, a thermoplastic elastomer other than the thermoplastic resin (A), a crosslinking agent (excluding the radically polymerizable compound (B) and the epoxy compound (C)), a monofunctional vinyl compound, an ultraviolet absorber, an antistatic agent, an antioxidant, a coupling agent, a plasticizer, a flame retardant, a colorant, a dispersant, an emulsifier, an elasticity reducing agent, a diluent, an antifoaming agent, an ion trapping agent, a thickener, a leveling agent, inorganic particles, organic particles, and the like.
[0091] Examples of the crosslinking agent include bismaleimide compounds and isocyanate compounds.
[0092] The resin composition may further contain a monofunctional vinyl monomer having one carbon-carbon double bond in the molecule, if necessary. By containing a monofunctional vinyl compound having one vinyl group, the molecular weight between crosslinking points of the cured product can be increased, which is preferable in that the degree of freedom of movement of the molecular chain is increased, making it easier to obtain a cured product with excellent flexibility. Examples of monofunctional vinyl compounds include monofunctional aliphatic (meth)acrylate compounds such as ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl acrylate, and isostearyl acrylate. The monofunctional aliphatic (meth)acrylate compound preferably has an alkyl group having 8 to 25 carbon atoms. The carbon number is more preferably 10 or more, even more preferably 12 or more, and even more preferably 15 or more. The carbon number is more preferably 20 or less. Specifically, at least one selected from the group consisting of isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, and isostearyl acrylate is preferred, and isostearyl acrylate is more preferred. When the carbon number of the alkyl group is within the above range, the compatibility of the thermoplastic resin (A) and the radical polymerizable compound (B) during curing is good, molecular chains are easily entangled with each other, and the crosslinking density is easily increased in a pseudo manner, so that the heat resistance of the obtained sheet cured product is good. When a monofunctional vinyl compound is contained, the content thereof is preferably from 0.5 to 50 parts by mass, and more preferably from 1 to 25 parts by mass, based on 100 parts by mass of the thermoplastic resin (A).
[0093] Examples of inorganic particles include calcium carbonate, magnesium carbonate, barium carbonate, magnesium sulfate, barium sulfate, calcium sulfate, zinc oxide, magnesium oxide, calcium oxide, titanium oxide, aluminum oxide, zinc oxide, alumina, aluminum hydroxide, hydroxyapatite, silica, magnesium silicate, mica, talc, kaolin, clay, glass powder, asbestos powder, zeolite, and clay silicate. Examples of the organic particles include (meth)acrylate-based resin particles, styrene-based resin particles, silicone-based resin particles, nylon-based resin particles, polyethylene-based resin particles, benzoguanamine-based resin particles, and urethane-based resin particles. When inorganic particles or organic particles are contained, the content thereof is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and still more preferably 15 parts by mass or more, per 100 parts by mass of the thermoplastic resin (A). On the other hand, the upper limit is preferably less than 400 parts by mass relative to 100 parts by mass of the thermoplastic resin (A), more preferably 350 parts by mass or less, even more preferably 300 parts by mass or less, particularly preferably 250 parts by mass or less, and even more preferably 80 parts by mass or less, more preferably 75 parts by mass or less, even more preferably 70 parts by mass or less, particularly preferably 50 parts by mass or less. When the content of inorganic particles or organic particles is equal to or more than the lower limit, the dielectric properties of the sheet cured product can be further reduced, and the linear thermal expansion coefficient of the sheet cured product can be reduced, so that peeling from the substrate is less likely to occur when used as a circuit board material. On the other hand, when the content of inorganic particles or organic particles is equal to or less than the upper limit, the moldability when forming the resin composition into a sheet is good. In order to enhance dispersibility, the inorganic particles may be surface-treated with a surface treatment agent as necessary.
[0094] <Physical properties of the resin composition> The present resin composition can have the following physical properties.
[0095] The adhesive strength of the present resin composition is appropriately determined depending on the material of the adherend, but for example, the adhesive strength to copper foil is preferably 0.7 kN / m or more, and particularly preferably 0.8 kN / m or more. By having the adhesive strength of 0.7 kN / m or more, when the present resin composition is used as a circuit board material, peeling or deformation does not occur. Specifically, the adhesive strength can be measured by the method described in the Examples below.
[0096] Furthermore, the adhesive strength of the present resin composition to polytetrafluoroethylene (PTFE) is preferably 0.3 kN / m or more, and particularly preferably 1.0 kN / m or more. In order to cope with the future trend toward higher communication frequencies, it is expected that the application of PTFE substrates with excellent low dielectric properties will expand. The adhesive strength of 0.3 kN / m or more is preferable in that it can be used as a circuit board material without peeling or deformation. Specifically, the adhesive strength can be measured by the method described in the Examples below.
[0097] The relative dielectric constant of the present resin composition after curing is preferably not more than 4, more preferably not more than 3, and even more preferably not more than 2.5. On the other hand, there is no particular lower limit for the relative dielectric constant, and it is sufficient if it is 1 or more. The dielectric loss tangent of the resin composition after curing is preferably 0.003 or less, more preferably 0.002 or less, and even more preferably 0.0015 or less. On the other hand, the lower limit of the dielectric loss tangent is not particularly limited, and it is sufficient that it is 0 or more. The above-mentioned dielectric constant and dielectric tangent were determined by measuring the cured material obtained by heat pressing the resin composition at 200°C and 2 MPa for 30 minutes as a test piece at a temperature of 23°C and a frequency of 10 GHz in accordance with JIS C2565:1992.
[0098] <Resin sheet> A resin sheet according to one embodiment of the present invention (hereinafter, also referred to as "the present resin sheet") is obtained by forming the present resin composition in an uncured state into a sheet shape.
[0099] The thickness of the present resin sheet is preferably from 10 to 500 μm, more preferably from 50 to 400 μm, and further preferably from 100 to 350 μm. When the thickness of the resin sheet is equal to or greater than the lower limit, the sheet has good handleability. When the thickness is equal to or less than the upper limit, the sheet has good conformability to steps in a circuit board when the sheet is used as a circuit board material.
[0100] <Laminate> In order to improve the handling properties of the present resin sheet, it is preferable to provide a release film on one or both surfaces to form a laminate. The release film may be, for example, a resin film mainly composed of polyolefin such as polyethylene or polypropylene, polyester such as polyethylene terephthalate or polyethylene naphthalate, polyimide, polycarbonate, etc. The peel strength may be adjusted by applying a silicone resin release agent or the like to the surface of these films. The thickness of the release film is preferably from 1 to 300 μm, more preferably from 5 to 200 μm, further preferably from 10 to 150 μm, and even further preferably from 20 to 120 μm. The surface of the release film that comes into contact with the resin sheet may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.
[0101] The laminate may be wound around a core to form a wound body. In the wound body according to one embodiment of the present invention, the length of the laminate is preferably 10 m or more, more preferably 20 m or more. By having a length of the laminate of 10 m or more, for example, when the resin sheet is used as a flexible laminate or a stretchable laminate, electronic components can be continuously produced, and the continuous film forming property is excellent. The upper limit of the length is not particularly limited, but it is preferably 1000 m or less. The material of the core is not particularly limited, but examples thereof include paper, resin-impregnated paper, acrylonitrile / butadiene / styrene copolymer (ABS resin), fiber-reinforced plastic (FRP), phenolic resin, resin containing inorganic matter, etc. An adhesive may be used for the core.
[0102] <Method of manufacturing resin sheet> Hereinafter, a method for producing the present resin sheet will be described, but the method for producing the present resin sheet is not limited to the following method.
[0103] [First manufacturing method] The first method for producing a resin sheet includes a coating liquid preparation step of preparing a coating liquid containing a resin composition, and a molding step of molding the coating liquid into a sheet.
[0104] (1) Coating fluid preparation process In the coating solution preparation process, the thermoplastic resin (A), the radically polymerizable compound (B), the epoxy compound (C), the curing agent (D), and optionally the organic peroxide (E), the curing aid (F), the solvent (G), and other components are stirred and mixed uniformly to obtain the coating solution. For mixing, a general mixing / stirring device such as a mixer, blender, three-roll kneader, ball mill, kneader, single-screw kneader or twin-screw kneader can be used, and heating may be performed during mixing, if necessary.
[0105] (2) Molding process In the forming step, the coating liquid is formed into a sheet to obtain a resin sheet. The coating liquid can be formed into a sheet by a known method. For example, the method may be a doctor blade method, a solvent casting method, or an extrusion film forming method. A preferred forming method includes a method including the following (2-1) coating step and (2-2) drying step.
[0106] (2-1) Coating process In the coating step, a coating liquid is applied to the surface of a release film to form a coating film. The coating method may be a common method such as a dip method, a spin coating method, a spray coating method, a blade method, etc. For coating, a coating device such as a spin coater, a slit coater, a die coater, a blade coater, a gravure coater, etc. can be used, and this makes it possible to uniformly form a coating film of a predetermined thickness on the release film.
[0107] (2-2) Drying process In the drying step, the solvent is removed from the coating film formed above. The drying temperature is not particularly limited, but is usually 10 to 150° C., preferably 25 to 120° C., and more preferably 30 to 110° C. When the drying temperature is equal to or lower than the upper limit, the crosslinking reaction of the radical polymerizable compound (B) in the coating film is suppressed. When the drying temperature is equal to or higher than the lower limit, foaming of the resin sheet is suppressed, and the solvent can be effectively removed, improving productivity. The drying time can be appropriately adjusted depending on the state of the coating film, the drying environment, etc. The drying time is preferably 30 seconds or more, more preferably 1 minute or more, and even more preferably 2 minutes or more. On the other hand, the drying time is preferably 1 hour or less, more preferably 30 minutes or less, and even more preferably 15 minutes or less. By setting the drying time to the above lower limit or more, the solvent can be sufficiently removed, whereas by setting the drying time to the above upper limit or less, the productivity can be improved and the production cost can be suppressed. The solvent in the resin composition can be removed by a known heating method such as using a hot plate, a hot air oven, an IR heating oven, a vacuum dryer, or a high-frequency heater.
[0108] From the viewpoints of preventing contamination of the surface of the resin sheet and of handling properties, a release film may be laminated on the resin sheet after the drying step.
[0109] [Second manufacturing method] The second method for producing the resin sheet includes a film-forming step of extruding a resin composition onto a release film.
[0110] In the film-forming process, the thermoplastic resin (A), the radically polymerizable compound (B), the epoxy compound (C), the curing agent (D), and optionally the organic peroxide (E) and other components are kneaded in a single-screw extruder or a twin-screw extruder, and extruded onto a release film using an extruder or the like under a temperature condition that is equal to or higher than the melting point of the thermoplastic resin (A) and lower than the crosslinking temperature of the radically polymerizable compound (B) and the epoxy compound (C) to form a film. The method for extruding the resin composition is not particularly limited, but a more specific example is T-die molding.
[0111] The curing temperature of the present resin composition may be any temperature at which the thermoplastic resin (A) does not flow and the crosslinking reaction of the radical polymerizable compound (B) and the epoxy compound (C) proceeds. Specifically, the curing temperature is preferably 120 to 300°C, more preferably 140 to 250°C, and even more preferably 150 to 220°C. The curing time of the present resin composition is not particularly limited, but is preferably from 10 minutes to 2 hours.
[0112] <Applications of resin composition and resin sheet> Applications of the present resin composition and the present resin sheet according to one embodiment of the present invention include, but are not limited to, copper foil laminates, stretchable substrates, flexible printed circuit boards, multilayer printed wiring boards, circuit board materials for electric and electronic devices such as capacitors, underfill materials, inter-chip fills for 3D-LSI, insulating sheets, vibration damping materials, adhesives, solder resists, semiconductor encapsulants, hole filling resins, and component embedding resins.
[0113] The resin composition of the present invention can be used as a circuit board material by laminating it with a conductor. When used as a circuit board material for electric and electronic devices, the resin composition may be formed into a resin sheet before use. The thickness of the resin sheet is preferably 10 μm or more and 500 μm or less. The thickness of the conductor is preferably 0.2 μm or more and 70 μm or less.
[0114] The conductor may be a metal foil made of a conductive metal such as copper or aluminum, or an alloy containing such a metal, or a metal layer formed by plating or sputtering.
[0115] <Circuit board materials> The circuit board material of the present invention can be produced, for example, by the following method. After the resin sheet according to one embodiment of the present invention is placed on a conductor, the resin sheet is heat cured to form an insulating layer, on which a further conductor is layered, and the required number of such layers are stacked. The curing temperature of the present resin sheet may be any temperature at which the thermoplastic resin (A) does not flow and the crosslinking reaction of the radical polymerizable compound (B) and the epoxy compound (C) proceeds. Specifically, the curing temperature of the present resin sheet is preferably 120 to 300°C, more preferably 140 to 250°C, and even more preferably 150 to 220°C. The curing time of the resin sheet is not particularly limited, but is preferably from 10 minutes to 2 hours. The lamination of the resin sheet and the conductor may be performed by directly laminating the resin sheet with a conductive metal foil, by bonding the resin sheet and the conductive metal foil with an adhesive, by forming a conductive metal layer by plating or sputtering, or by a combination of these methods. The method may also include a step of drilling holes in the insulating layer to form via holes, and a step of roughening the surface of the insulating layer. EXAMPLES
[0116] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples and comparative examples, various physical properties were measured by the following methods.
[0117] <Raw materials> [Thermoplastic resin (A)] a-1: Styrene-ethylene-butadiene-styrene block copolymer (SEBS: Asahi Kasei Corporation, "Tuftec H1052"), styrene content 20% by mass, storage modulus (24°C) = 6.2 MPa, density = 0.890 g / cm 3
[0118] [Radical polymerizable compound (B)] b-1: Triallyl isocyanurate (TAIC: manufactured by Shinryo Corporation), mass average molecular weight (Mw): 250
[0119] [Epoxy compound (C)] c-1: 1,6-Hexanediol diglycidyl ether (Mitsubishi Chemical Corporation, "YED216D"), epoxy equivalent: 116g / eq c-2: Tripropylene glycol diglycidyl ether (Kyoeisha Chemical Co., Ltd., "Epolight 200P"), epoxy equivalent: 200g / eq c-3: Bisphenol AF diglycidyl ether (Mitsubishi Chemical Corporation, "YX7660"), epoxy equivalent: 237g / eq
[0120] [Hardening agent (D)] d-1: A mixture of 4-methylhexahydrophthalic anhydride and hexahydrophthalic anhydride (manufactured by New Japan Chemical Co., Ltd., "Rikacid MH-700")
[0121] [Organic peroxide (E)] e-1: α,α-di(tert-butylperoxyisopropyl)benzene (manufactured by NOF Corporation, "Perbutyl P")
[0122] [Hardening agent (F)] f-1: 2-ethyl-4-methylimidazole (Tokyo Chemical Industry Co., Ltd.)
[0123] Solvent f-1: Toluene (content > 99.0% by mass)
[0124] <Examples 1 to 3, Comparative Examples 1 to 2> The raw materials were mixed in the ratio shown in Table 1, and heated at about 80°C to completely dissolve the raw materials to prepare a resin composition. The prepared resin composition was spread in a sheet shape on the release-treated surface of a 50 μm-thick release film (PET film manufactured by Mitsubishi Chemical Corporation) that had been subjected to a silicone release treatment, so that the thickness after drying would be 100 μm, and heated in an oven at 100°C for 15 minutes to volatilize the solvent. A 50 μm-thick release film (PET film manufactured by Mitsubishi Chemical Corporation) that had been subjected to a silicone release treatment was laminated on the surface of the resin composition from which the solvent had been volatilized, so that the release-treated surface faced the resin sheet, to prepare a resin sheet with a release film.
[0125] In addition, a resin sheet with a release film having a resin thickness of 20 μm was prepared in the same manner as above, except that the resin composition having the composition shown in Table 1 was spread into a sheet so that the thickness after drying would be 20 μm.
[0126] <Evaluation> The resulting resin composition was subjected to the following evaluations, and the results are shown in Table 1.
[0127] (1) Dielectric properties The resin sheets with release films having a resin thickness of 100 μm produced in the Examples and Comparative Examples were held in a heat press at 200° C. for 30 minutes while applying a pressure of approximately 2 MPa to completely harden the resin sheets, and the release films on both sides were peeled off to obtain a cured resin composition. The in-plane relative dielectric constant and dielectric loss tangent of the cured resin sheet were measured in TE mode using a cavity resonator (manufactured by AET) and a network analyzer MS46 122B (manufactured by Anritsu Corporation). The measurement frequency was 10 GHz.
[0128] (2) Copper adhesion The resin sheet with a release film having a resin thickness of 20 μm produced in the examples and comparative examples was cut into 5 cm×10 cm. The release film was peeled off from the resin sheet, and the matte surface of a copper foil (manufactured by Fukuda Metal Foil Powder Co., Ltd., “CF-T4X-SV”) having a thickness of 18 μm was laminated on both surfaces, and the resin sheet was completely cured by applying a pressure of about 2 MPa with a heat press machine at 200° C. for 30 minutes to obtain a laminate. The obtained laminate was cut into a width of 1 cm to prepare a measurement sample. The obtained measurement sample was subjected to a T-shaped peel test using a universal testing machine (manufactured by Shimadzu Corporation) at a chuck distance of 25 mm, at a peel speed of 50 mm / min in an environment of 23° C., and the peel strength was measured.
[0129] (3)PTFE adhesiveness The resin sheet with a release film having a resin thickness of 20 μm produced in the examples and comparative examples was cut into 5 cm×10 cm. A PTFE substrate (manufactured by Rogers, “RT5880”) having a thickness of 18 μm was laminated on both surfaces of the resin sheet from which the release film was peeled off, and the resin sheet was completely cured by holding it for 30 minutes while applying a pressure of about 2 MPa with a heat press machine at 200° C. to obtain a laminate. The obtained laminate was cut into a width of 1 cm to prepare a measurement sample. The obtained measurement sample was subjected to a T-shaped peel test using a universal testing machine (manufactured by Shimadzu Corporation) at a chuck distance of 25 mm, at a peel speed of 50 mm / min in an environment of 23° C., and the peel strength was measured.
[0130] [Table 1]
[0131] From Examples 1 to 3, it was confirmed that a resin composition containing a thermoplastic resin (A), a radical polymerizable compound (B), an epoxy compound (C) and a curing agent (D), in which the content of the thermoplastic resin (A) is 20 mass% or more relative to the total mass of the resin composition, and the sum of the contents of the epoxy compound (C) and the curing agent (D) is more than 0 mass% and less than 4 mass% relative to the total mass of the resin composition, has excellent low dielectric properties and adhesion to copper foil. Among them, Example 3 using a fluorine-containing epoxy resin also has excellent adhesion to PTFE, and it was shown to have excellent adhesive properties for members of a wide range of materials. On the other hand, Comparative Example 1 did not contain the epoxy compound (C) and the curing agent (D) and had poor adhesion to the copper foil. In Comparative Example 2, the sum of the contents of the epoxy compound (C) and the curing agent (D) was 4 mass% or more relative to the total mass of the resin composition, and the adhesion to the copper foil was insufficient and the dielectric properties tended to deteriorate.
Claims
1. A resin composition comprising at least one thermoplastic resin (A) selected from the group consisting of a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, an ethylene-based polymer, and a cyclic polyolefin resin copolymer, a radically polymerizable compound (B), an epoxy compound (C), and a curing agent (D), wherein the content of the thermoplastic resin (A) is 20 mass% or more with respect to the total mass of the resin composition, and the sum of the contents of the epoxy compound (C) and the curing agent (D) is more than 0 mass% and less than 4 mass% with respect to the total mass of the resin composition.
2. The resin composition according to claim 1, wherein the thermoplastic resin (A) contains a styrene-based thermoplastic elastomer, and the styrene content of the styrene-based thermoplastic elastomer is 10% by mass or more and 70% by mass or less.
3. The resin composition according to claim 1, wherein the thermoplastic resin (A) has a mass average molecular weight (Mw) of 30,000 or more.
4. The resin composition according to claim 1, wherein a content of the radically polymerizable compound (B) relative to 100 parts by mass of the thermoplastic resin (A) is 1 part by mass or more and 50 parts by mass or less.
5. The resin composition according to claim 1, wherein a sum of the contents of the thermoplastic resin (A) and the radically polymerizable compound (B) is 30 mass% or more with respect to a total mass of the resin composition.
6. The resin composition according to claim 1, wherein the epoxy compound (C) comprises a polyfunctional epoxy compound having an epoxy equivalent of 1000 g / eq or less.
7. The resin composition according to claim 1 , comprising an acid anhydride-based curing agent and / or an active ester-based curing agent as the curing agent (D).
8. 2. The resin composition according to claim 1, wherein a cured product obtained by heat pressing the resin composition at 200° C. and 2 MPa for 30 minutes has a dielectric loss tangent of 0.003 or less at a frequency of 10 GHz.
9. A resin sheet comprising the resin composition according to any one of claims 1 to 8.
10. A laminate comprising the resin sheet according to claim 9 and a release film on one or both surfaces thereof.
11. A circuit board material comprising an insulating layer formed from a cured product of the resin composition according to any one of claims 1 to 8 and a conductor laminated thereon.
Citation Information
Patent Citations
Polyphenylene ether resin composition, prepreg, metal-clad laminate, and printed wiring board
JP2010059363A
Resin composition, prepreg, laminate, resin sheet, printed wiring board and semiconductor device
JP2012255059A
Cyclic olefin resin composition, and substrate provided from said resin composition
WO2006095511A1